Introducing Beginners to Making: Spaces, Methods, and Hands-on Approaches: Workshop for Building Pathways to Creativity and Innovation in Education (Constructionism Conference Proceedings, 2025)
Despite the increasing relevance of constructionist learning approaches, many educators struggle with how to introduce students to Making in a structured, accessible, and scalable way – especially when resources, space, or institutional support are limited. This workshop addresses that challenge by presenting three practical models for integrating Making into formal education: (1) a dedicated school-based Makerspace, (2) a mobile Makerspace with tools on wheels, and (3) an extracurricular Makerspace. Each model is illustrated with examples from practice and designed to accommodate different school contexts and infrastructure constraints.Drawing on Papert’s constructionism (Papert & Harel, 1991) and expanded through the MakeComp4School framework (Maurer, 2023), the workshop introduces two didactic entry strategies: the „Maker License“ system, which scaffolds skill acquisition before students begin independent projects, and situational making, which invites learners to address real-world needs through self-directed prototyping. Both models promote creativity, agency, and interdisciplinary thinking (Marshall & Harron, 2018) while maintaining a low-threshold entry into hands-on making.Participants will engage in rapid prototyping tasks using accessible materials (e.g., cardboard, basic electronics, microcontrollers) and receive implementation resources such as planning templates and evaluation tools. This workshop contributes to the field of constructionist learning by providing educators with pedagogically grounded, adaptable methods to foster meaningful making experiences for beginners.